A Sociolinguistic Study Of English-Indonesian Code Mixing Used In KARNISA Magazine - Wijayanti, Henny Kusuma (2012)
This paper has three objectives. They are identifying the forms of code mixing, describing the types of code mixing, and describing the motives of code mixing used in Karnisa Magazine. The objects of this research are the English codes mixing that are found in Karnisa Magazine. The type of this research is descriptive qualitative research. The data of this research are the English-Indonesian code mixing in the forms of sentences used in the articles of Karnisa Magazine on edition 38th-44th, 2007-2010. In collecting the data, the writer uses documentation method. Based on the analysis the researcher finds three findings, there are: firstly, there are five forms of code mixing used in Karnisa Magazine. There are found 43 data of word or 37,4 %, 36 data of phrase or 31,3 %, 3 data of hybrid or 2,6 %, 2 data of reduplication word or 1,7 %, and 31 data of clause or 27 %. Secondly, the types of code mixing found in Karnisa Magazine are 115 data of outer code mixing or 100 %. Thirdly, the motives of using code mixing in Karnisa Magazine are classified into two motives: Prestige filling motive are 94 data or 81,7 % and need filling motive are 21 data or 18,3 %.